Knowledge of lexicon of Dubrovnik's speech among non-native speakers of Croatian language - Jeljenić, Ljubica; Konsuo Kuzmanić, Marija (ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023., 2026)
Language is an extremely dynamic creation prone to frequent changes and adaptations. Changes are not only visible at the level of the language as a standard, but also relate to the areas of dialects and local speech. All local speech is undergoing numerous changes, primarily due to the influence of globalization, media communication, but also the standard language. Despite the strong influence of the modern way of life and technological progress, the lexicon of the Dubrovnik speech recorded in the dictionaries of the Dubrovnik speech Škrinja uspomena - Dubrovački jezični pabirci by Melita Bego-Urban, Naški - Dubrovački rječnik by Davor Mladošić and Maja Milošević, and the Dictionary of the Dubrovnik Speech by Mihajlo Bojanić and Rastislava Trivunac is still preserved and used in everyday communication. Therefore, the main focus of the paper is precisely the Dubrovnik speech and its reception by non-native speakers. More specifically, the paper attempts to examine the knowledge of the lexicon of Dubrovnik speech on a selected corpus of words from everyday life (food, clothing, household) of non-native speakers of the Croatian language who reside in the area of Dubrovnik and its immediate surroundings.